2018
DOI: 10.1111/mpp.12690
|View full text |Cite
|
Sign up to set email alerts
|

Oxylipins from both pathogen and host antagonize jasmonic acid‐mediated defence via the 9‐lipoxygenase pathway in Fusarium verticillioides infection of maize

Abstract: Oxylipins are a newly emerging group of signals that serve defence roles or promote virulence. To identify specific host and fungal genes and oxylipins governing the interactions between maize and Fusarium verticillioides, maize wild-type and lipoxygenase3 (lox3) mutant were inoculated with either F. verticillioides wild-type or linoleate-diol-synthase 1-deleted mutant (ΔFvlds1D). The results showed that lox3 mutants were more resistant to F. verticillioides. The reduced colonization on lox3 was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 59 publications
9
53
0
Order By: Relevance
“…The spectra showed a virtually identical fragmentation to the corresponding spectra of [ Figure S2, supporting information), but this occurred with isotope scrambling. 12-OPDA can be isomerized to iso-OPDA by heating, 24 but the retention of four and five 2 This fragmentation suggested that one 2 H atom of the anions at m/z 166 and 182 was derived from C-6.…”
Section: Ms/ms Analysis Of [M-h]mentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra showed a virtually identical fragmentation to the corresponding spectra of [ Figure S2, supporting information), but this occurred with isotope scrambling. 12-OPDA can be isomerized to iso-OPDA by heating, 24 but the retention of four and five 2 This fragmentation suggested that one 2 H atom of the anions at m/z 166 and 182 was derived from C-6.…”
Section: Ms/ms Analysis Of [M-h]mentioning
confidence: 99%
“…Oxylipins designate oxygenated unsaturated C 18 fatty acids formed by plants and microorganisms, in many cases associated with potent biological activities . Of particular interest is the biosynthesis of (+)‐7‐ iso ‐jasmonic acid (JA) by plants, which has been investigated in detail due to its biological importance .…”
Section: | Introductionmentioning
confidence: 99%
“…In addition to salicylic acid, plant lipid metabolites are important signal molecules in local and systemic defense against pathogens [59]. More specifically, fungal and plant oxylipins (including the well-known jasmonic acid), produced via the oxidation of polyunsaturated fatty acids, have a primordial role as signals in plantpathogen ecosystems [60]. Fungal oxylipins attempt to reprogram PTI and, in turn, the host counteracts by producing its own oxylipins to impede pathogen infection: However, fungal oxylipins can also induce Effector Triggered Susceptibility (ETS) by activating genes of the host oxylipin pathway, such as ZmLOX3, that suppress defense-related branches of the maize oxylipin pathway and favor Fusarium verticillioides virulence and fumonisin accumulation [60,61].…”
Section: Candidate Genesmentioning
confidence: 99%
“…PO pathways result in structurally diverse metabolites with key biological activities. POs, especially jasmonic acid (JA), function as vital signalling molecules in plant growth and development (e.g., flower and pollen development, seed maturation) and in plant stress responses [4,7,[22][23][24][25][26][27][28][29]. Through its precursor [12-oxo-phytodienoic acid (OPDA)] and its derivatives, JA also plays key roles in plant defences against herbivores and certain pathogens, mainly necrotrophic [25,29,30].…”
mentioning
confidence: 99%